Rad bi čebelaril: zbirka nasvetov za vse, ki se odločate za prvi panj (University of Maribor Press, 2018)
I’d like to be a Beekeeper : A Collection of Tips for Everyone Choosing the First Own Hive. As the role and importance of bees are invaluable today, the United Nations General Assembly quite rightly declared 20 May as World Bee Day in December 2017 at the initiative of Slovenia. The guide entitled I Want to Be a Beekeeper is the result of a project selected in the tender procedure “Project work with public and non-profit sector – Student innovative projects for social benefits 2016–2018”, co-funded by the Ministry of Education, Science and Sport of the Republic of Slovenia and the European Union from the European Social Fund. It contains advice to help future beekeepers decide whether to start beekeeping or not. The authors answer the usual questions asked by beginners: how to get started in beekeeping, where to acquire adequate knowledge, what equipment to purchase, what is the initial investment, what are beekeeping tasks, how much time beekeeping takes, which are members of a honey bee colony, how to take care of bee health, what to do in case of an allergic reaction to a bee sting and many others. Moreover, it contains instructions for beekeeper registration and calculation of the real price of honey. When we work with bees, we are in contact with nature, resulting in favourable psychophysical effects. Bee products bring joy to people throughout the year. Beekeeping can be a gainful activity as well as a hobby to spend quality leisure time. It requires, though, specific skills and perseverance, and above all responsibility. And this is the central message of the I Want to Be a Beekeeper guide. Normally, you will not get rich by keeping bees, but you can enjoy it immensely.